Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/healthcare11010089
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Coping Strategies Used by Transgender Individuals in Response to Stressors during and after Gender-Affirming Treatments—An Explorative Study

Abstract: Background: Gender-affirming treatments are reported to improve mental health significantly. However, a substantial number of transgender individuals report a relapse in, or persistence of, mental health problems following gender-affirming treatments. This is due to multiple stressors occurring during this period, and in general as a consequence of widespread stigma and minority stress. Aim: The aim of this pilot study was to identify different coping strategies that transgender individuals use in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Negative worker-employer relations and less favorable coping styles could lead to ‘being the extra-productive worker’ and, due to the repetitiveness of GAC visits and needing time off from work, using personal vacation instead of medically certified leave ending in a strained work-life balance. These findings of stressful GAC management are in line with the literature [ 48 ]. Legislative support, such as medical absences and transition-related paid absence, can therefore inherently be a positive influence on the work-life-GAC balance apart from personal views.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Negative worker-employer relations and less favorable coping styles could lead to ‘being the extra-productive worker’ and, due to the repetitiveness of GAC visits and needing time off from work, using personal vacation instead of medically certified leave ending in a strained work-life balance. These findings of stressful GAC management are in line with the literature [ 48 ]. Legislative support, such as medical absences and transition-related paid absence, can therefore inherently be a positive influence on the work-life-GAC balance apart from personal views.…”
Section: Discussionsupporting
confidence: 92%
“…It is challenging to compare GAC-related work absences due to limited research [ 37 ] and differences in design and gender diversity in an earlier study [ 11 ], while our study had a more balanced sample and reported more detail of GAC. Moreover, as indicated by Oorthuys et al [ 48 ], receiving GAC can be burdensome and can affect the work-life balance, as emphasized by our interviewees, leading to several types of work absences of which our survey only reports sick days. When comparing the latter, TM and GD individuals’ sick leave was similar as their personalized journey did not always include surgery as gender-affirming hormonal therapy was more reported by them.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As illustrated, findings from our study contribute to a growing body of literature, suggesting that achieving gender congruence, engaging in practices that elevate the wider community, and experiencing gender pride, are important processes that promote wellbeing among TGDN individuals (Oorthuys et al, 2023;Valente et al, 2020;van den Brink et al, 2020). While the capacity for these findings to have real world clinical implications depends upon their replication in future studies with larger and more diverse samples, several tentative practical implications are proposed.…”
Section: And Practical Implicationsmentioning
confidence: 55%
“…Mentoring programs present one potential avenue through which TGDN individuals can gain access to, or engage as positive role models (Matsuno & Israel, 2018). Family and peer support have been found to foster greater self-acceptance, less psychological distress, and more help-seeking among transgender individuals (Oorthuys et al, 2023;Valente et al, 2020). Similarly, engagement in community activism plays a facilitative coping role and expands access to community connections and services (Budge et al, 2012;Frost et al, 2019;Riggle et al, 2011).…”
Section: And Practical Implicationsmentioning
confidence: 99%